Direct electron paramagnetic resonance monitoring of the peptide synthesis coupling reaction in polymeric support - Nakaie, Clovis R.; Malavolta, Luciana; Schreier, Shirley; Trovatti, Eliane; Marchetto, Reinaldo [UNESP] (Elsevier B.V., 2006)
This work demonstrates, for the first time. a time-resolved electron paramagnetic resonance (EPR) monitoring of a chemical reaction occurring in a polymeric structure. The progress of the coupling of a N-alpha-tert-butyloxycarbonyl-2.2.6.6-tetramethylpiperidine-1-oxyl-4-amino-4-carboxylic acid (Boc-TOAC) spin probe to a model peptide-resin was followed through EPR spectra. Progressive line broadening of EPR peaks was observed, indicative of an increased population of immobilized spin probe molecules attached to the solid support. The time for spectral stabilization of this process coincided with that determined in a previous Coupling study. thereby validating this in situ quantitative monitoring of the reaction. In addition, the influence of polymer swelling degree and solvent viscosity, as well as of the steric hindrance within beads. on the rate of coupling reaction was also addressed. A deeper evaluation of the latter effect was possible by determining unusual polymer parameters such as the average site-site distance and site-concentration within resin beads in each solvent system. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: peptide; polymer; electron paramagnetic resonance